Abracadabra 4.0: pre-diploma ePoster presentation / Nur Afiqah Ab Latif, Aileen Mohd Adam and Rasaya Marimuthu - Ab Latif, Nur Afiqah; Mohd Adam, Aileen; Marimuthu, Rasaya (Academy of Language Studies, 2022)
After two years of having online competitions due to the pandemic, the Academy of Language Studies (UiTMCPP) has successfully organised face-to-face Abracadabra 4.0: Pre-Diploma Competition this semester. Abracadabra 4.0 is a poster presentation competition that aims to increase self-confidence and strengthen English language ability, specifically for Pre-diploma students. The theme for this semester is ‘Ain’t No Other Place but Mother Earth’. The competition started with the selection of the finalists from 27 June 2022 to 8 July 2022. The two best groups from Pre-diploma classes (PBA0021A and PBA0021B) were selected to compete in the final round held on 14 July 2022 at Bilik Perdana (BP1). The titles presented were ‘Deforestation’, ‘Air Pollution’, ‘Animal Extinction: Orangutans’ and ‘Zero Waste at Home’. The juries consisted of Associate Professor Dr Rofiza Aboo Bakar, Dr Isma Noornisa Ismail and Puan Norhafizah Abdul Halil.